Interpreting green consumer behaviour - Zuha Rosufila Abu Hasan (United Kingdom : Cardiff University, 2012)
Despite the popularity of consumers’ environmental behaviour choices, little research has been forthcoming which analyzes green behaviour across different situations in a systematic way. A particularly relevant stream of research to explain the situational effect on consumer environmental behaviour is the Behavioural Perspective Model (BPM). A key insight of the BPM is of the anticipated benefit consumers acquire and the impact of the environment that surrounds consumer choice.